Microbiological analysis of manipulators and handling surfaces of public schools (Research, Society and Development, 2019)
Contaminated foodborne diseases are mainly caused by the lack of proper sanitation of food handlers as well as the surfaces on which they are handled. The objective was to perform the microbiological analysis of the hands of manipulators and manipulation surfaces in schools of a municipality of Maranhão. Microbiological analyzes were performed on the hands of ten food handlers and five handling surfaces. Total and thermotolerant coliform counts were determined using the Most Probable Number Multiple Tubes method. It was verified that only one manipulator did not present contamination by the microorganisms studied, and in relation to the handling surfaces all presented contamination. Therefore, it was verified that in the evaluated schools all presented deficiencies in the process of hygiene of the hands and the surfaces.